The Impact of Comorbid Anxiety on College Student Response to an ADHD Coaching Treatment - Kininger, Rachel (East Carolina University, 2019)
Attention-deficit/hyperactivity disorder (ADHD) creates profound impairments. Even when K-12 school-based interventions are successful and students with ADHD matriculate to college, there is a high likelihood of college dropout, failing grades, substance use, dangerous driving, and risky sexual behavior. Unfortunately, there are few proven mental health treatments for college students with ADHD, and little is known about what works for whom. The present study examined the acceptability and efficacy of ADHD coaching for college students and examined the moderating impact of anxiety on psychoeducational outcomes. Fifty-nine students were randomly assigned to ADHD coaching (n = 30) or a control condition (n = 29). Consistent with previous research, students were significantly more satisfied with ADHD coaching and rated the intervention as significantly more acceptable than students in the control condition. The main effect of ADHD coaching was inconclusive, but a small positive effect on grade point average (GPA) was noted. Results from simple moderation analyses were similarly inconclusive, but trends tentatively suggest that high levels of anxiety may be a risk factor for self-reported psychoeducational outcomes but also may confer treatment benefit for academic outcomes. Recruiting large samples of college students representing a wide range of trait anxiety appears necessary to examine the impact of comorbid anxiety on psychoeducational outcomes.
Keywords: coaching; College students--Mental health--Treatment; Attention-deficit-disordered youth--Treatment; Counseling in higher education; Comorbidity